Optimization of tobacco seed cleaning modes - E. A. Bubnov; D. V. Don (Новые технологии)
The process of obtaining high-quality tobacco seeds is very laborious, and at present many operations are performed manually at All-Russian Research Institute of Tobacco, Makhorka and Tobacco Products. The process of obtaining tobacco seeds at the Institute consists of the following operations: harvesting of inflorescences, drying of inflorescences, destruction of inflorescences, screening out coarse impurities, final cleaning in an air stream. An attempt was made earlier to mechanize and improve working conditions at the stage of final purification of the seed mixture. A unit for the final purification of tobacco seeds was developed, manufactured and tested. In this article other modes of final purification of the tobacco seed mixture to improve mechanization and productivity of the same unit have been tested. The seed mix of the 2019 harvest has been used in the studies. Coarse impurities have been separated from the seed mix by sieving through sieves with different hole sizes. Earlier modes of double final purification of seed mixture were proposed. In this research the previously proposed double cleaning modes have been taken as control ones, and in the experiment three-fold modes with a higher feed rate of the seed mixture have been used. As a result, the experimental modes provide identical removal of contaminants, however, the productivity of the unit increases 2 – 3 times due to the shorter total duration of purification, and mechanization is also improved due to a more uniform flow of the seed mixture. In this case, there is no need for the constant presence of an operator, and the process of final purification of the tobacco seed mixture is reduced only to its loading and unloading.